2019
DOI: 10.1021/acsami.9b14757
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Backbone Regioregularity on High-Mobility Conjugated Polymers Based on Alkylated Dithienylacrylonitrile

Abstract: We designed and synthesized two donor–acceptor type conjugated polymers, the regioirregular polymer RI-PDPP-CNTVT-6 and its regioregular counterpart RR-PDPP-CNTVT-6, based on diketopyrrolopyrrole (DPP) and alkylated dithienylacrylonitrile (CNTVT) units. Among them, the 2-decyltetradecyl side chain on the DPP acceptor unit and the hexyl side chain on the CNTVT donor unit were used to ensure enough solubility for them. The backbone regioregularity was used to tune electronic structures and carrier transport of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Thermionic emission is a common model to describe the electron injection at room temperature, which has been applied successfully for organic semiconductors with metal contacts. Thermionic emission model follows an Arrhenius-type relationship 45 = * − Δ i k j j j y { z z z J A E kT exp (7) where J is the injection current and A* = 4πqm*k 2 T 2 /h 3 . Here, m* is the effective mass of electron in the metal, k is the Boltzmann constant, h is Planck's constant, and T is the operational temperature (298 K).…”
Section: Charge Carrier Dynamics In Ofets Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermionic emission is a common model to describe the electron injection at room temperature, which has been applied successfully for organic semiconductors with metal contacts. Thermionic emission model follows an Arrhenius-type relationship 45 = * − Δ i k j j j y { z z z J A E kT exp (7) where J is the injection current and A* = 4πqm*k 2 T 2 /h 3 . Here, m* is the effective mass of electron in the metal, k is the Boltzmann constant, h is Planck's constant, and T is the operational temperature (298 K).…”
Section: Charge Carrier Dynamics In Ofets Withmentioning
confidence: 99%
“…Organic field-effect transistors (OFETs) as key components of organic electronics have been researched for the applications in displays, sensors, identification tags, and so on. The past several decades have witnessed huge success in high-performance OFETs. The carrier mobility of p-type OFETs is now comparable to or even better than that of silicon-based transistors. However, the consumerization of OFETs still suffers challenges because of their significant bias-stress instability. Bias-stress instability of OFETs manifests as a shift of threshold voltage and a decrease in drain current over operation time, which leads to gradual malfunctioning of devices in real applications. For instance, a liquid crystal display driven by an OFET might not turn on/off appropriately because of the threshold voltage shift.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al compared the performance of the OFET fabricated using the regioregular polymer P70 with that using the regioirregular polymer P71 containing the alkylated dithienylacrylonitrile (CNTVT) and DPP units (Figure 5). 35 The surface morphologies of P70 and P71 were studied. It was observed that regioirregular P71 was rougher than regioregular P70.…”
Section: Dpp-derived Polymers For Ofet'smentioning
confidence: 99%
“…[29][30][31] In particular, the electronic properties of such polymers can be engineered easily through chemical modification. [32][33][34] Furthermore, most conjugated polymers can be soluble in common solvents. The unique advantages of conjugated polymers open up a new avenue for diverse applications, including organic fieldeffect transistors (OFETs), [35][36][37][38] organic photovoltaic cells (OSCs), [39][40][41] and organic light-emitting diodes (OLEDs).…”
Section: Introductionmentioning
confidence: 99%